Digital Transformation Strategies of MSMEs in Samarinda City: An Analysis of Challenges, Opportunities, and Their Impact on Local Competitiveness - Indra Maulana; Dedy Rahmatullah; Mega Norsita; Siti Monashafa; Atiiqah Daffaa (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The accelerated growth of digital technologies has reshaped business environments, creating new opportunities and competitive pressures particularly for micro, small, and medium enterprises (MSMEs). In Samarinda City, MSMEs play a central role in driving local economic activity, yet their level of digital adoption remains uneven. This study analyzes digital transformation strategies implemented by MSMEs in Samarinda, identifies challenges and opportunities, and examines their implications for local competitiveness. Using a descriptive-quantitative design, data were collected through structured questionnaires distributed to MSME actors in culinary, fashion, and creative-service sectors. The findings reveal varying levels of digital readiness influenced by digital literacy, cost barriers, infrastructure limitations, and policy support. MSMEs that adopted digital tools such as e-commerce platforms, digital payments, and social media marketing reported higher efficiency, improved market access, and stronger brand positioning. The study highlights the need for coordinated interventions involving government, academia, and industry associations to strengthen digital capability and ensure sustainable local competitiveness